2009
DOI: 10.1063/1.3072024
|View full text |Cite
|
Sign up to set email alerts
|

Planar patterned media fabricated by ion irradiation into CrPt3 ordered alloy films

Abstract: Planar patterned media using CrPt3 ordered alloy films were fabricated by Ar+ or Kr+ ion irradiation through nanoimprinted or electron beam lithography made masks. CrPt3 ordered alloy film on fused quartz substrate exhibits a large perpendicular anisotropy of 5×106 erg/cc and a large coercivity of 12 kOe, and we found that its magnetic order (magnetization) was completely suppressed by a quite low Ar+ or Kr+ ion dose of about 1–2×1014 ions/cm2. Magnetic force microscope image of the ion-beam patterned CrPt3 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The first two methods involve the removal of the material between dots or the assembly of the particles, which leads to non-uniformity in the height of the disk surface and causes a head-floating problem for nearcontact recording. 1 However, in the last method, an FM film undergoes local changes to a soft magnetic, 5 paramagnetic (PM), 6 or antiferromagnetic (AF) 7 phase without surface asperity by ion irradiation or atomic diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The first two methods involve the removal of the material between dots or the assembly of the particles, which leads to non-uniformity in the height of the disk surface and causes a head-floating problem for nearcontact recording. 1 However, in the last method, an FM film undergoes local changes to a soft magnetic, 5 paramagnetic (PM), 6 or antiferromagnetic (AF) 7 phase without surface asperity by ion irradiation or atomic diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, tracks or bits are magnetically isolated by the area where the saturation magnetization (M s ) or the perpendicular anisotropy (K u ) are reduced by implanting non-magnetic ions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] We previously reported that larger reduction of the M s in the ion-implanted area was important for obtaining higher signal quality. 15 On the other hand, a masked area needs to be protected from the process damages of the ion implantation.…”
mentioning
confidence: 97%
“…6 Recently, we have reported ion irradiation BPM using CrPt 3 ordered alloy films. [7][8][9] The CrPt 3 alloy film has a large perpendicular magnetic anisotropy, 10,11 and the magnetization of CrPt 3 can be suppressed by a quite low dose of ion irradiation associated with the phase change from ordered L1 2 to disordered A1 phases. Thus, the CrPt 3 is considered to be a candidate of high-density ion irradiation BPM with magnetically isolated bits.…”
mentioning
confidence: 99%
“…Thus, the CrPt 3 is considered to be a candidate of high-density ion irradiation BPM with magnetically isolated bits. 7 However, high-temperature heat treatment at 850 C is required to synthesize the L1 2 CrPt 3 , which is a problem for the practical application of CrPt 3 .…”
mentioning
confidence: 99%